Web Development of Maria Bakery Tayu Based on Qris Using Waterfall Method - Hariyanto, Marcellino Kevin; Nugroho, Agus Cahyo; Chandrawati, Thecla Brenda (Journal of Business and Technology, 2024)
A website is a page that contains certain information and can be accessed easily by anyone, anytime and anywhere via the internet. With the rapid development of technology, websites are also often used as a place to buy and sell online, whether food products, goods or reservations and much more. To place an order through the website, it is necessary to have a system that supports ordering, order processing and payment. This research uses the waterfall method to create an online ordering web from a bakery called Maria Bakery. The rapid development of technology it allows us to be easier to order or buy something because it is much more efficient and can also be done anywhere and anytime.